Boosting Financial Satisfaction Among Civil Servants Though Smart Money Management - Asandimitra, Nadia; Kautsar, Achmad; Nihaya, Ina Uswatun; Aji, Tony Seno (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The periodic increase in civil servants’ (PNS) income, coupled with their significant numbers, highlights the necessity of assessing financial satisfaction levels among civil servants in East Java. Beyond income, key influencing factors include financial knowledge, financial strain, and the adoption of a hedonistic lifestyle. This is particularly relevant given that millennials, known for their consumptive behavior, make up the largest portion of the civil servant workforce. This study investigates financial management behavior as a mediating variable in these relationships. An explanatory research design was employed, targeting all civil servants in East Java. A purposive sampling technique identified four major cities and districts with the highest numbers of civil servants: Surabaya, Sidoarjo, Malang, and Jember. Using the Slovin formula, a sample size of 330 participants was determined, distributed equally across the selected areas. Path analysis, utilizing SmartPLS 3.0, was chosen as the data analysis technique. The study’s findings reveal that financial strain, a hedonistic lifestyle, and income significantly influence financial management behavior. Interestingly, financial knowledge does not impact financial management behavior. Furthermore, financial satisfaction is significantly affected by financial strain and a hedonistic lifestyle, while financial knowledge and income do not have a significant effect on financial satisfaction. Crucially, financial management behavior mediates the relationship between a hedonistic lifestyle and financial satisfaction effectively. However, it does not successfully mediate the effects of financial knowledge, financial strain, or income on financial satisfaction.